On Some Ostrowski Type Integral Inequalities - Agli´c Aljinovi´c, Andrea; Hoxha, Razim; Peˇcari´c, Josip (Sarajevo Journal of Mathematics, 2024)
In this paper we establish some new Ostrowski type integral inequalities, by using the Montgomery identity and Taylor's formula. 2000 Mathematics Subject Classification. 26D15